2013
DOI: 10.2478/s11756-013-0287-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of Nlrp9a, Nlrp9b and Nlrp9c during mouse development

Abstract: Abstract:The Nlrp gene family contains 20 members in the mouse. Recent studies have demonstrated that these genes play key roles in reproduction. In this study, we investigated the expression patterns of Nlrp9a, Nlrp9b and Nlrp9c in the mouse. In 2-week-old mouse tissues, Nlrp9a, Nlrp9b and Nlrp9c were all strikingly expressed in the ovary, while the transcripts of Nlrp9b and Nlrp9c were also detected in other tissues. The transcripts of Nlrp9a, Nlrp9b and Nlrp9c were restricted to the oocytes and declined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…In the mouse, Nlrp7, Nlrp8, Nlrp11 and Nlrp13 have been lost; however, Nlrp2, Nlrp5 and Nlrp14 accumulate during oogenesis and are essential for the normal development of preimplantation embryos (Tong et al , 2000; Hamatani et al , 2004; Peng et al , 2012). Meanwhile, Nlrp4a–Nlrp4g and Nlrp9a–Nlrp9c display specific or preferential ovary expression patterns (Dade et al , 2004; Hamatani et al , 2004; Peng et al , 2013, 2014a). In addition, the latest studies have indicated that Nlrp4g is an oocyte-specific gene in the mouse (Peng et al , 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse, Nlrp7, Nlrp8, Nlrp11 and Nlrp13 have been lost; however, Nlrp2, Nlrp5 and Nlrp14 accumulate during oogenesis and are essential for the normal development of preimplantation embryos (Tong et al , 2000; Hamatani et al , 2004; Peng et al , 2012). Meanwhile, Nlrp4a–Nlrp4g and Nlrp9a–Nlrp9c display specific or preferential ovary expression patterns (Dade et al , 2004; Hamatani et al , 2004; Peng et al , 2013, 2014a). In addition, the latest studies have indicated that Nlrp4g is an oocyte-specific gene in the mouse (Peng et al , 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that expressed sequence tags corresponding to mouse Nlrp4a, 4c, 4e, 4f, 9b and 9c were found in cDNA libraries of oocytes, zygotes and two‐cell stage embryos supports this notion . Several published reports validated the high expression levels of mouse Nlrp2, Nlrp4a‐f , Nlrp5, Nlrp9a‐c and Nlrp14 in female and male gonads and maturing gametes . They also showed that mRNA expression levels of these NLRs drop steeply shortly after fertilization towards the blastocyst stage, a characterizing feature of maternal effect genes .…”
Section: A Phylogenetic Nlr Cluster Implicated In Reproductive Functionsmentioning
confidence: 71%
“…In contrast, the exact functions of NLRP9 in reproductive systems have remained mysterious until recently. Early studies have proposed that human, murine and bovine NLRP9 were selectively expressed in oocytes, ovaries and testes, 10‐15 and as a result, NLRP9 has been implicated to function in preimplantation embryo development 16 . While neither simultaneous knockout of NLRP9a and NLRP9c nor single knockdown of NLRP9b affected early embryonic development in mice, 17,18 a recent study discovered that female mice deficient in all three isoforms of NLRP9 had defective blastocyst development and increased lethality in the preimplantation embryos 19 .…”
Section: Nlrp9 Isoforms and Reproductive Functionsmentioning
confidence: 99%